Pulvinar quantitative susceptibility mapping predicts visual hallucinations post‐deep brain stimulation in Parkinson's disease - Keita Matsuura; Yuichiro Ii; Masayuki Maeda; Ken‐ichi Tabei; Masayuki Satoh; Maki Umino; Hiroyuki Kajikawa; Tommohiro Araki; Naoko Nakamura; Hirofumi Matsuyama; Akihiro Shindo; Hidekazu Tomimoto (Brain and Behavior, 2023)
Abstract Purpose We have reported the relationship between low pulvinar nuclei (PN) intensity in susceptibility‐weighted imaging and the appearance of visual hallucinations and cognitive function. The aim of the study was to examine the changes in the quantitative susceptibility mapping (QSM) in patients with Parkinson's disease (PD) who underwent deep brain stimulation (DBS) and verify whether the PN susceptibility value (SV) on QSM can predict visual hallucination and cognitive changes after DBS. Methods This study examined 24 patients with PD who underwent DBS along with QSM imaging on magnetic resonance imaging (MRI). All MRIs were performed within 3 months before surgery. The PN SV was further assessed based on the QSM. Then, associations were examined among cognitive changes, hallucination, and PN SV. The cognitive function of the patient was compared immediately before surgery and at 1 year postoperatively. Results Visual hallucinations were observed in seven patients during the follow‐up period. The PN SV was ≥0.045 ppm in nine patients with PD, and six of them had visual hallucinations, whereas only one of 15 patients with PD with SV of <0.045 ppm had visual hallucinations (Fisher's exact test, p = .0037). Conclusions The SV of >0.045 ppm at the PN in QSM in patients with PD may provide useful information suggesting visual hallucination and cognitive deterioration after DBS treatment.